2014
DOI: 10.1371/journal.pone.0107202
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tumor Suppressor Genes Based on Gene Ontology and the KEGG Pathway

Abstract: Cancer is a serious disease that causes many deaths every year. We urgently need to design effective treatments to cure this disease. Tumor suppressor genes (TSGs) are a type of gene that can protect cells from becoming cancerous. In view of this, correct identification of TSGs is an alternative method for identifying effective cancer therapies. In this study, we performed gene ontology (GO) and pathway enrichment analysis of the TSGs and non-TSGs. Some popular feature selection methods, including minimum redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 107 publications
0
42
0
Order By: Relevance
“…Enrichment between lncRNA and EBV genes can be represented by the hypergeometric test P value [8789] of the target gene of lncRNA, L(i), and the target gene of EBV, V(j), which can be computed by: p(i,j)=p(L(i),V(j))=k=mn(Mm)(NMnm)(Nn) where N represents the total number of human genes, M and n represent the number of target genes of EBV gene j and the number of target genes of lncRNA i, respectively, and m represents the number of lncRNA target genes that also target genes of EBV gene j. The smaller the P value for a lncRNA and an EBV gene, the stronger the suggested association between them.…”
Section: Methodsmentioning
confidence: 99%
“…Enrichment between lncRNA and EBV genes can be represented by the hypergeometric test P value [8789] of the target gene of lncRNA, L(i), and the target gene of EBV, V(j), which can be computed by: p(i,j)=p(L(i),V(j))=k=mn(Mm)(NMnm)(Nn) where N represents the total number of human genes, M and n represent the number of target genes of EBV gene j and the number of target genes of lncRNA i, respectively, and m represents the number of lncRNA target genes that also target genes of EBV gene j. The smaller the P value for a lncRNA and an EBV gene, the stronger the suggested association between them.…”
Section: Methodsmentioning
confidence: 99%
“…94% (n = 145) of the genes expressed in control cells were expressed at lower mRNA levels in JVM13-D1 T286A cells ( Figure 5D). To explore whether this mRNA downmodulation would include tumor suppressor genes (TSGs), we compiled a set of 583 genes defined as TSGs (32). We found that 30 of 33 (91%) expressed TSGs were downregulated in JVM13-D1 T286A cells.…”
Section: Resultsmentioning
confidence: 99%
“…For a given GO term GO j and a gene g , let G 1 be a gene set consisting of genes annotated to GO j and G 2 be another gene set consisting of neighbor genes of g in the protein-protein interaction network reported in STRING (http://string-db.org/) [26], a well-known public database providing known and predicted protein-protein interactions. The GO enrichment score between GO j and g is defined as the −log 10 of the hypergeometric test P value [2730] of G 1 and G 2 , which can be calculated by T1ESGOg,GOj=log10false∑k=mnMkNMnkNn,where N is the number of genes in human, M is the number of genes in G 1 , n is the number of genes in G 2 , and m is the number of common genes of G 1 and G 2 . A large enrichment score between GO j and g indicates close relationship between them.…”
Section: Methodsmentioning
confidence: 99%